The Role of School Culture in Shaping A Positive Learning Environment - Feriana, Dita; Ulfatun, Titik (Jayapangus Press, 2024)
Education plays an important role in improving the quality of learning for both teachers and students. Therefore, schools must have a good school culture, so that every school community can be given a place and opportunity to optimize the potential that exists in each of them. The purpose of this study is to analyze the role of school culture in forming a positive learning environment for accounting students of SMK Batik 1 Surakarta. This research is included in qualitative research using a descriptive study approach. The research techniques used were interviews, observations, and documentation studies. The sampling method in this study was purposive sampling. The samples used were 3 students from class 11 Ak. 2, then the deputy head of student affairs and accounting teacher. The results describe the school culture in shaping a positive environment including School Facilities and Infrastructure, Teacher Interaction with Students, Student Interaction with students, disciplining students, language and communication, school regulations.